Pelatihan Pembuatan Foto Produk Untuk Penguatan Visual Branding Dalam Pemasaran Online Produk KSU Kowage - Elmira Siska; Nurlaela Eva Puji Lestari; Siti Mabrur Rachmah; Lela Elvira (Forum Kerjasama Pendidikan Tinggi, 2023)
This community service activity was carried out with a partner, KSU Kowage, which is one of the MSME cooperatives in Bogor Regency. Apart from small capital, the problems faced by the KSU KOWAGE Cooperative are weak human resources, limited access to information, and the use of technology in carrying out online marketing. This activity aims to improve the skills of KSU Kowage members in creating aesthetic product photos that can be used as promotional media in online marketing, to strengthen the visual branding of MSME products. Implementation of community service activities is carried out through three stages which include the preparation stage, implementation stage, and activity evaluation stage. Based on the recapitulation analysis of the questionnaires given to participants, it is known that the material provided is by the participant's needs. Based on the paired sample t-test statistical test using the SPSS version 25 program, this training actually had a positive and significant impact on increasing insight, knowledge, skills, and expertise of KSU Kowage members